2022
DOI: 10.1002/adsu.202200407
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Additive Manufacturing Feedstocks for Fabricating High Voltage, Low‐Cost Aqueous Supercapacitors

Abstract: day life. However, managing the endof-life of plastic materials has become an increasingly urgent topic due to the reliance of most virgin plastics production on non-renewable resources like oil, and the significant, harmful effects that environmentally persistent waste plastic can have on the natural world. [1] Limiting these effects requires consumption of virgin plastic to be reduced wherever possible, and where not possible, plastic waste should be recycled into new products such that it does not enter tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…40 Compared to the use of conventional electrodes, AM allows for the production of electrodes with bespoke geometries at significantly lower manufacturing timescales and costs, by simply altering the computational design. 41,42 There are significant issues still to address within AM electrochemistry, such as the need to "activate" the surface of the electrode to reveal conductive materials, 34 surface fouling (as seen with conventional commercial electrodes), and the ingress of solutions into the plastic. 43 These issues have led to the majority of AM electrodes (AMEs) being single-use items.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 Compared to the use of conventional electrodes, AM allows for the production of electrodes with bespoke geometries at significantly lower manufacturing timescales and costs, by simply altering the computational design. 41,42 There are significant issues still to address within AM electrochemistry, such as the need to "activate" the surface of the electrode to reveal conductive materials, 34 surface fouling (as seen with conventional commercial electrodes), and the ingress of solutions into the plastic. 43 These issues have led to the majority of AM electrodes (AMEs) being single-use items.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the development of bespoke filaments is being increasingly reported. , AM now spans a wide range of electrochemical applications, with many published reports on its use in fuel cells, batteries, , supercapacitors, and electroanalytical sensing devices. , The latter began with the printing of simple “lollipop” shape (or disk) working electrodes , but has progressed further to electrodes of varying geometries and the electrochemical cell itself; even accessories and electrochemical experimental equipment has been reported . Compared to the use of conventional electrodes, AM allows for the production of electrodes with bespoke geometries at significantly lower manufacturing timescales and costs, by simply altering the computational design. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 Currently, these AMEs must be used as single-shot electrodes, similar to SPEs, because of solution ingress into the electrodes, 73 among other issues. However, due to the flexibility, low-cost, and rapid prototyping capabilities of AM (in addition to the recent reports of the use of recycled conductive feedstocks 74 ), we expect many further reports in this field over the coming years.…”
Section: ■ Electroanalytical Approachesmentioning
confidence: 99%
“…Outstanding papers in the literature revealed that the polymeric materials can be reusable by numerous ways, (i) recycling carbon fibers and using them as additive option in the fused filament fabrication (FFF) process of PLA, (ii) reusing glass fiber obtained from turbine blades to reinforce the mechanical properties of PLA material, (iii) recycling PET and polypropylene aim for manufacturing additive filaments with similar mechanical proprieties to the commercial filament and, (iv) combining waste of PLA recovered from coffee pods with native poly­(ethylene glycol) and carbon black particles aim for manufacturing a suitable option of conductive additive filament that can be dedicate to constructed electrodes. , However, to the best of our knowledge, the aforementioned studies do not explore residues of thermoplastic as binder structures for manufacturing disposable electrochemical sensors, which are of high potential in the modern analytical chemistry field, including forensic, , pharmaceutical, environmental, , food and biological ones. …”
Section: Introductionmentioning
confidence: 99%